Construction of carbon quantum dots/single crystal TiO2 nanosheets with exposed 001 and 101 facets and their visible light driven catalytic activity. Issue 7 (25th January 2019) - Huang, Hongqin; Ouyang, Hao; Han, Tiehu; Wang, Huigang; Zheng, Xuming
Abstract : Carbon quantum dots were doped into anatase TiO2 single crystal nanosheets (TNS) with highly exposed 001 and 101 reactive facets by a facile solvothermal process. Abstract : Carbon quantum dots were successfully doped into anatase TiO2 single crystal nanosheets (TNS) with exposed 001 and 101 reactive facets by a facile solvothermal process. SEM and TEM confirmed the as-prepared TiO2 nanosheet structure and that the dominant exposed face is the 001 facet, and the loaded N-CDs are nearly spherical with an average size of about 3 nm. XPS results confirmed that the deposited N-CDs were chemically integrated into the TiO2 nanosheets. UV-vis DRS spectroscopy shows that with the dotting of N-CDs, the absorption edge of N-CDs/TNS has been extended into the visible light region. The ability of the N-CDs/TNS to degrade Rhodamine B (RhB) in aqueous solution under visible light irradiation ( λ ≥ 400 nm) was investigated. The results show that the photocatalytic performance of N-CDs/TNS was substantially improved relative to pure TNS. The photodegradation efficiency reached its maximum value with 6 mL of N-CDs/TNS, showing a 9.3-fold improvement in photocatalytic activity over TNS. Fluorescence spectroscopy (PL) and electron paramagnetic resonance (EPR) studies were conducted to characterize the active species during the degradation period, based on which the possible photodegradation mechanism of N-CDs/TNS by visible light irradiation was given.